Stimulating Consumer Interest in Pukis Kota Baru: Food Influencer and Sustainable Value Through Hedonic and Utilitarian Value - Ayu RIka Putri; Michelle Anastasia (Yayasan Ilomata, 2026)
This study investigates the influence of food influencers and sustainable value on consumers’ intention to purchase Pukis Kota Baru, a traditional Indonesian food, examining the mediating roles of hedonic value and utilitarian value. Amid the rapid digitalisation of consumption and the heightened importance of sustainability in consumer decisions, there remains limited empirical research integrating influencer marketing and sustainability within the context of traditional foods. Addressing this gap, the present research adopts a quantitative survey method, targeting active social media users in DKI Jakarta who have prior experience with Pukis Kota Baru, and analyses responses from 259 participants using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. The findings reveal that both food influencers and sustainable value exert a direct positive effect on consumption intention, while only utilitarian value serves as a significant mediator in these relationships; hedonic value does not play a mediating role. These results underscore the predominance of functional considerations in shaping purchase intentions for traditional foods in the digital era, and highlight the strategic importance for marketers and MSMEs to emphasise sustainability messages and practical benefits in digital marketing campaigns for local food products.